2001
DOI: 10.1590/s1413-86702001000400007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of rotavirus infections in Minas Gerais, Brazil

Abstract: In order to develop good polices regarding public health measures and vaccine use to prevent rotavirus induced gastroenteritis, the epidemiology of the illness in various regions of Brazil is necessary. Accordingly, this study was to detect the frequency and types of rotavirus in one city in a tropical part of Brazil. This is an epidemiological survey of pediatric gastroenteritis caused by rotavirus conducted in Juiz de Fora, Minas Gerais State, Brazil. We analyzed 656 in-patient (190) and out-patient (466) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(22 reference statements)
1
1
1
1
Order By: Relevance
“…Peak incidence of positive tests was between May and August, the winter months. This agrees with other studies done in temperate climate regions [14] and Brazilian studies done in Southern, Southeastern and Central-West Brazil [10,15,16]. Temporal occurrence of diarrhea admissions for children and deaths from diarrhea in Brazil occur in winter, suggesting the importance of rotavirus infection as cause of gastroenteritis in this patient population [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Peak incidence of positive tests was between May and August, the winter months. This agrees with other studies done in temperate climate regions [14] and Brazilian studies done in Southern, Southeastern and Central-West Brazil [10,15,16]. Temporal occurrence of diarrhea admissions for children and deaths from diarrhea in Brazil occur in winter, suggesting the importance of rotavirus infection as cause of gastroenteritis in this patient population [17].…”
Section: Discussionsupporting
confidence: 90%
“…Various studies in Brazilian populations have indicated that about 2/3 of rotavirus infections occur in children under two years of age [4,10,15,16]. In our study, we found only 44.5% of positive cases in this age group (data not shown).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The persistency of various etiological agents remains a serious public health concern. In Latin America and the Caribbean region, as in other developing geographic regions, rotavirus is one of the most common causal agents of viral diarrhea in young children [7,9,14,17,23,28,29]. However, other agents such as diarrheagenic Escherichia coli strains, Salmonella, Shigella and Aeromonas spp, Campylobacter yeyuni, Yersinia enterocolitica and parasites have been also described [1,11,18,19,25].…”
Section: Introductionmentioning
confidence: 99%
“…Os segmentos genômicos codificam para um grupo de seis proteínas estruturais (VPs, viral proteins), encontradas nas partículas virais, e outras cinco proteínas nãoestruturais (NSPs, non-structural proteins) presentes somente em células infectadas e não observadas em partículas maduras SILVA et al, 2001;MASCARENHAS et al, 2002; SECRETARIA DO ESTADO DE SÃO PAULO, 2004). O principal sítio de replicação viral é o intestino delgado, no jejuno mais especificamente nas células epiteliais maduras que revestem as microvilosidades intestinais deste local; desencadeando um fenômeno de má-absorção e diarréia (ESTES, 2001;BRASIL, 2006).…”
Section: Doenças De Transmissão Hídrica Causadas Por Vírus Entéricosunclassified